ANALISIS PENETAPAN MARGIN KEUNTUNGAN MURABAHAH PADA BANK SYARIAH DI INDONESIA - Ahadi, Mu’thial; Zulhilmi, Muhammad; Isnaliana, Isnaliana (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2023)
Murabahah financing is a form of buying and selling financing with certain benefits added on top of the acquisition cost, where repayment can be made in cash or in installments. This study aims to look at the factors determining murabahah profit margins. The researcher uses a qualitative descriptive approach using primary data, library research, literature studies, and is also supported by related topics obtained from the web and information sources on Islamic banking. The results showed that the factors with the greatest potential in determining margins were internal factors (overhead costs, financing volume, profit targets, third party funds and acquiring costs) and external factors (BI rate and market competition).